A Meta-analysis: Effect of Stem Cells Transplantation on Rehabilitation of Diabetes Mellitus with Limb Ischemia - Yongjin LIU; Bo DU; Bowei HUANG; Suping HUANG (康复学报)
Objective:To systematically review the effect of stem cells on the rehabilitation of diabetes mellitus with limb ischemia.Methods:We electronically searched databases including PubMed, FMRS, SCI, CNKI, WanFang and VIP databases to collect randomized controlled trials (RCTs) about the rehabilitation of diabetes mellitus with limb ischemia which published before October 2016. Two reviewers independently screened literature, extracted data and assessed the risk of bias of included studies. Then, Meta-analysis was performed by using RevMan 5.3 software.Results:A total of 5 RCTs were included. The results of Meta-analysis showed that stem cells therapy had advantage over conventional therapy. Compared with the control group, stem cells therapy had positive effect on the levels of ABI [WMD=0.14, 95%CI (0.10, 0.19), P<0.000 01], the score of rest pain [WMD=-1.52, 95%CI (-1.84, -1.21), P<0.000 01] was reduced significantly, the rate of ulcer healing [RR=2.21, 95%CI (1.54, 3.16), P<0.000 1] was increased, the rate of new collateral vesse [RR=3.12, 95%CI (1.65, 5.89), P=0.000 5] was increased, and the rate of amputation [RR=0.12, 95%CI (0.02, 0.59), P=0.010] was reduced.Conclusion:Existing evidence suggested that stem cells therapy is effective on the rehabilitation of diabetes mellitus with limb ischemia to some degree. Nevertheless, due to the limited quantity and quality of included studies, large-scale, multicenter, and high quality RCTs are required to verify the conclusion.